PENGARUH LINGKUNGAN SOSIAL TERHADAP MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN MUKHTAR SYAFA’AT BLOKAGUNG BANYUWANGI - Mahmudah, Mahmudah; Afada, Sherif; Jauhariyah, Nur Anim (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2024)
The purpose of this study was to analyze the influence of the social environment on learning motivation and the contribution given to students at the Mukhtar Syafa'at 1 Putra Blokagung Banyuwangi Islamic Boarding School. The research approach used quantitative causality research. The population in this study were all students at the Mukhtar Syafaat Islamic Boarding School totaling 100 people. The sample in this study was 78 students with a simple random sampling technique. Data collection used observation, questionnaire, and documentation methods. For data analysis using the linear regression method. The results of the study showed a calculated t of 2.415> t table 1.664 so that it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of the social environment on learning motivation. While in the correlation test, the correlation value r = 0.267 was obtained which means that the two variables have a low linear relationship but have a positive value, meaning that the higher the level of influence from the social environment, the higher the level of student learning motivation. The R Square value = 0.071, meaning that the contribution given by the social environment to learning motivation is 7.1%, while the remaining 92.9% is influenced by other factors not examined in this study.